PENGARUH PENGELUARAN PEMERINTAH DAN JUMLAH UANG BEREDAR TERHADAP PRODUK DOMESTIK BRUTO INDONESIA TAHUN 2004-2018 - Kinanti Asa Mutia; Lucia Rita Indrawati (Universitas Tidar, 2019)
The condition of the Indonesian economy in 2008 experienced a slight upheaval due to the global economic crisis and is currently in a stage of development where the population is increasing, the workforce is increasing and demand for goods is also increasing. Indonesia is projected to experience a phase of demographic bonus which can be a threat if the government does not prepare well. At present the objectives of the Macro economy are Economic Growth. The purpose of this study is to determine the effect of government spending and the money supply on Indonesia's gross domestic product from 2004-2018. To explain the effect of government spending and the partial money supply on gross domestic product, this study uses time series data from 2004-2018. The variables to be observed are government expenditure and the amount of money in circulation and gross domestic product. Data was obtained from Bank Indonesia, the BPS-Statistic Indonesia and the Ministry of Finance. This study shows the results that Government Expenditures and Circulating Money Significantly Influence Indonesia's Gross Domestic Product in 2004-2018.. Keywords: Government expenditure, money supply and gross domestic product (GDP) of Indonesia